Employer expectations on the performance of graduates through KSA (knowledge, skills and attitudes) with reference to banking sector in Muscat, Sultanate of Oman - Shinde, Dr. Sandip; Al Balushi, Qais; Al Rashdi, Al Yaqdhan; Adam Al-Zadjali, Majid; Hameed Al Shabibi, Abdul (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study is to find out the gap between employer expectations and performance of graduates through KSA (Knowledge, skills and attitude) approach in banking sector in Muscat, Sultanate of Oman. The main area which has been covered in this research is related to expectations and performance of graduates through knowledge, skills and attitude. Questionnaire for the survey was designed to find out the gap between expected and actual performance of graduates through KSA. To analyze the findings, descriptive and correlation analysis has been used. The results of the analysis are very important and significant for employers, graduates who have recently joined the banking sector and educational institutions. Firstly, Educational institutions should work on scaling up the skills of the graduates. Secondly, organizations should scale down the expectations from the new employees and also should work on enhancing their capabilities. Thirdly, graduates who have recently joined banking sector should work on enhancing their knowledge, skills and attitude required for the organization.The conclusion leads to recommendations to the educational institutions as well as employer to modify their curriculum and training programs to enhance the capabilities of the new employees.Keywords: KSA, Knowledge, Skills, Attitudes, Employer expectations.